English Idioms in Use. 60 units of vocabulary reference and practice Self-study and classroom use - McCarthy M. Michael (Cambridge, Cambridge University Press, 2005)
English Idioms in Use is a vocabulary book for good intermediate level learners and above. It is primarily designed as a self-study reference and practice text but it can also be used for classroom work. English Idioms in Use: 60 easy-to-use two-page units: idioms are presented and explained on left-hand pages with a range of practice exercises on right-hand pages. Presents and explains idioms in typical contexts using short texts and clear example sentences. Based on the most frequently used idioms from a corpus of written and spoken English and from the Cambridge International Dictionary of Idioms. Provides valuable information about appropriate usage. Promotes good learning habits with study tips and follow-up tasks. Contains a comprehensive, student-friendly answer key. Includes a detailed index to help you find the idioms you are interested in.